2011
DOI: 10.1007/s10592-011-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Removing exogenous information using pedigree data

Abstract: Management of certain populations requires the preservation of its pure genetic background. When, for different reasons, undesired alleles are introduced, the original genetic conformation must be recovered. The present study tested, through computer simulations, the power of recovery (the ability for removing the foreign information) from genealogical data. Simulated scenarios comprised different numbers of exogenous individuals taking part of the founder population and different numbers of unmanaged generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 28 publications
2
42
1
Order By: Relevance
“…However, with the pedigree-based method, the maximum level of removal was achieved in just one generation of management [14], thus on this time scale, it is more efficient. With the molecular-based method, an equivalent level of removal to that obtained with the pedigree-based method was achieved only at the second generation of management (not shown), but it continued to increase in subsequent generations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the pedigree-based method, the maximum level of removal was achieved in just one generation of management [14], thus on this time scale, it is more efficient. With the molecular-based method, an equivalent level of removal to that obtained with the pedigree-based method was achieved only at the second generation of management (not shown), but it continued to increase in subsequent generations.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we used pedigree data as source of information to remove introgressed genetic material and recover the native genetic background [14]. Different introgression events were simulated with a varying number of exogenous individuals entering the population and different numbers of generations during which exogenous genetic material was admixed.…”
Section: Introductionmentioning
confidence: 99%
“…Amador et al [24] proposed two other approaches to reduce migrant contributions. Their first approach was to minimize migrant contributions in the offspring population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, all approaches proposed in this paper aim at increasing the probability that alleles originating from native founders are not IBD. Amador et al [24] concluded that even with only a few generations without management, a small amount of introgression can spread into the population and it may be almost impossible to recover. This was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, strategies should also be aimed to gradually recover the specific genetic composition of that population. For such a task we may use the genealogical information (if we can trace back to the moment exogenous individuals entered the population) or molecular information (if marker data on the genetic constitution of population before the undesired introgression took place are available; Amador et al, 2011). However, these data are rarely available and, therefore, 'purification' must be based on other information.…”
Section: Introductionmentioning
confidence: 99%